2018
DOI: 10.1111/ijfs.13846
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different oleogels in processed cheese products formulation

Abstract: Summary This study investigates the potential usage of unsaturated vegetable oil oleogel to replace solid milk fat in processed cheese products (PCPs). Soybean oil was gelled using rice bran wax (RBW) or sunflower wax (SW) at two different concentrations and used to produce PCPs with final concentrations of 0.5% or 1% wax. An ungelled oil PCP and a commercial milk fat processed cheese (CC) were produced for comparison. Upon compositional analysis, moisture and fat content were similar between oleogel PCPs (OPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 35 publications
2
39
0
1
Order By: Relevance
“…This was due to the MC oleogel acting as a physical barrier that helped reduce the movement of gluten networks (Patel et al, 2014a). The successful applications of oleogels on hardness, spreadability, and stickiness in cream cheese and processed cheese products are also reported by the Maleky group (Bemer et al, 2016;Huang et al, 2018). As mentioned before, the authors linked their observation to the similarity in the solid fat network between the oleogels and controlled products.…”
Section: Textural Properties Of Oleogels For Food Applicationsmentioning
confidence: 81%
See 3 more Smart Citations
“…This was due to the MC oleogel acting as a physical barrier that helped reduce the movement of gluten networks (Patel et al, 2014a). The successful applications of oleogels on hardness, spreadability, and stickiness in cream cheese and processed cheese products are also reported by the Maleky group (Bemer et al, 2016;Huang et al, 2018). As mentioned before, the authors linked their observation to the similarity in the solid fat network between the oleogels and controlled products.…”
Section: Textural Properties Of Oleogels For Food Applicationsmentioning
confidence: 81%
“…Cream cheese and processed cheese products High oleic soybean; soybean; Rice bran wax; ethycellulose and sunflower wax Bemer et al, 2016;Huang et al, 2018;Park et al, 2018 Ice 2017incorporated β-carotene in EC oleogels and demonstrated that the oleogelation reduced the degradation of β-carotene compared to β-carotene in just oil, thus elevating its bioaccessibility. These examples serve as a library of possible beneficial oleogel properties suitable for food applications.…”
Section: Dairy Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Milk fat contained by the cheese products was replaced by soybean oil gelled using rice bran wax or sunflower wax, and the final concentrations of waxes in the cheese products was as low as 0.5% or 1%. The rheological and thermo-mechanical analysis resulted in comparable properties, such as hardness, storage modulus, and meltability, between the products based on wax oleogel and the control samples obtained with commercial milk fat [94]. The utilization of gelled oil in processed cheese products resulted in a less expensive product, with a reduced content of milk fat, no added chemicals or processing agents and also improved physicochemical properties of low solid fat cheese products.…”
Section: Cream Cheesementioning
confidence: 87%